Pest categorisation of Curtobacterium flaccumfaciens pv. flaccumfaciens. (31st May 2018) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health performed a pest categorisation of the seed‐borne bacterium Curtobacterium flaccumfaciens pv. flaccumfaciens . The pest is regulated in Council Directive 2000/29/EC (Annex IIB) as a harmful organism whose introduction into, and spread within, the protected zones (PZ) of Greece, Portugal and Spain shall be banned if present on seeds of Phaseolus vulgaris and of Dolichos . The bacterium is widely distributed outside the EU and causes a systemic vascular disease (bacterial wilt of bean) as well as bacterial tan spot disease on soybean. The pest was sporadically recorded in several EU Member States in the past, but is currently not known to occur in the EU. The identity of the bacterium is well established and identification methods are available. The major host is common bean ( Phaseolus vulgaris ), but other crops and weeds are, or may be, hosts or play a role as reservoirs, with uncertainties. Seed transmission remains uncertain for minor and alternative host species. The main pathway for entry is seed. The role of other pathways (e.g. irrigation water and infected residues) is uncertain. Should the bacterium enter the EU (including the PZ), it may establish, spread and have an impact on its host crops. The use of healthy seeds is the most effective control measure. Curtobacterium flaccumfaciens pv. flaccumfaciens fits all the criteria assessed by EFSA to be regarded as a Union quarantine pest.